Association of joint exposure to organophosphorus flame retardants and phthalate acid esters with gestational diabetes mellitus: a nested case-control study - Qi Lang; Xianfeng Qin; Xiangyuan Yu; Shudan Wei; Jinyan Wei; Min Zhang; Chaochao Zhao; Jun Zhang; Dingyuan Zeng; Xiaoying Zhang; Bo Huang (BMC, 2024)
Abstract Background Organic phosphate flame retardants (OPFRs) and phthalate acid esters (PAEs) are common endocrine-disrupting chemicals that cause metabolic disorders. This study aimed to assess the association between joint exposure to OPFRs and PAEs during early pregnancy in women with gestational diabetes mellitus (GDM). Methods Seven OPFRs and five PAEs were detected in the urine of 65 GDM patients and 100 controls using gas chromatography-tandem triple quadrupole mass spectrometry (GC-MS). The association of OPFRs and PAEs with GDM was assessed using logistic regression, weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) models. Results Levels of dibutyl phthalate (DBP), di-2-ethylhexyl phthalate (DEHP), diethyl phthalate (DEP), dimethyl phthalate (DMP), tris (2-butoxyethyl) phosphate (TBEP), tributyl phosphate (TBP), tris (2-chloroethyl) phosphate (TCEP), tris (1,3-dichloro-2-propyl) phosphate (TDCPP), tri-ortho-cresyl phosphate (TOCP), and triphenyl phosphate (TPHP) increased in the GDM group, and the OPFRs and PAEs, except for BBP and TMCP, were associated with GDM in the logistic regression analysis. In the WQS model, the mixture of OPFRs and PAEs was significantly positively associated with GDM (OR = 3.29, 95%CI = 1.27-8.51, P = 0.014), with TDCPP having the highest WQS index weight. BKMR analysis reinforced these results, showing that the overall association of joint exposure to the OPFRs and PAEs with GDM increased at exposure levels of the 55th to 75th percentiles. Independent exposure to TDCPP (OR = 1.42, 95%CI = 1.09-1.86, P = 0.011) and TBEP (OR = 1.29, 95%CI = 1.04-1.60, P = 0.023) were associated with an increased risk of GDM. Conclusions Environmental exposure to OPFRs and PAEs is significantly associated with GDM. These findings provide evidence for the adverse effects of exposure to OPFRs and PAEs on the health of pregnant women.